Failure of Ciprofloxacin Therapy in the Treatment of Community-Acquired Acute Pyelonephritis caused by In-Vitro Susceptible Escherichia coli Strain Producing CTX-Type Extended-Spectrum β-Lactamase - Seok, Hyeri (Infect Chemother, 2018)
While carbapenems are the drug of choice to treat extended-spectrum-β-lactamase (ESBL)-producing strains, some alternative carbapenem-sparing regimens are suggested for antibiotic stewardship. We experienced a case of ciprofloxacin treatment failure for acute pyelonephritis caused by an apparently susceptible Escherichia coli. A 71-year-old woman presented the emergency department with fever for 7 days and bilateral flank pain for 2 days. The laboratory results and abdominopelvic computed tomography finding were compatible with acute pyelonephritis. During 3-day ciprofloxacin therapy, the patient remained febrile with persistent bacteremia. After the change in antibiotics to ertapenem, the patient’s clinical course started to improve. ESBL-producing E. coli isolates were identified in all three consecutive blood samples. Pulsed-field gel electrophoresis (PFGE) patterns, serotypes, and sequence types showed the three isolates were derived from the identical strain. The isolates produced CTX-M-14 type ESBL belonging to the ST69 clonal group. Despite in vitro susceptibility, the failure was attributed to a gyrA point mutation encoding Ser83Leu within quinolone resistance-determining regions. This case suggests that ciprofloxacin should be used cautiously in the treatment of serious infections caused by ciprofloxacin-susceptible, ESBL-producing E. coli, even in acute pyelonephritis because in-vitro susceptibility tests could fail to detect certain genetic mutations.